Q-MAPS: INOVASI PLATFORM PRIVAT KURSUS AL-QURAN BERBASIS ONLINE-TO-OFFLINE (O2O) SYSTEM - Bakhtiar, Inayah Aqilah; Azahro, Fatimah Nur; Badres, Zakiyah (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
ABSTRACT Indonesia, despite having the largest Muslim population in the world, still faces challenges in achieving optimal engagement with the Qur’an due to unequal acces to Qur’anic education. Common obstacles include societal preceptions, limited accessibility for teachers and learners, and lack of infrastructure. Consequently, Qur’an learning outcomes remain suboptimal. Meanwhile, rapid technological development in Indonesia offers vast potential, though often misused for unproductive purposes. Adressing this issue, an innovative solution emerges through the integration of quranic education with technology, resulting in the development of Q-Maps, a private Qur’an tutoring application inspired by the Gojek service model and enhanced with an Online-to-Offline(O2O) system. This platform aims to improve Qur’an learning by combining digital connectivity with face-to-face interaction. Q-Maps connects student with qualified Qur’an teachers specializing in tajwid and tahfidz, offering flexible schedule, direct interaction, and e-Wallet payment system at affordable rates based on selected programs. The study is qualitative, using library research and descriptive analysis methods through journals, articles, and websites. The outcome is a Q-Maps prototype thet promotes easy, effective Qur’an learning while fostering the positive use digital technology in religious education. ABSTRAK Indonesia memiliki jumlah penduduk muslim terbesar di dunia. Namun kesadaran masyarakat dalam pembelajaran Al-Qur’an masih kurang optimal akibat terbatasnya akses pembelajaran yang merata. Faktor-Faktor seperti persepsi negatif terhadap pembelajaran Al-Qur’an serta keterbatasan akses bagi pengajar dan pelajar menjadi kendala utama. Di sisi lain, perkembangan teknologi di Indonesia sangat pesat, sayangnya perkembanganini sering disalahgunakan untuk hal-hal yang kurang bermanfaat. Berdasarkan problematika tersebut, muncul inovasi berupa Q-Maps yakni aplikasi kursus privat mengai yang mengadopsi sistem Online-to-Offline (O2O) seperti layanan Gojek. Q-Maps bertujuan mengoptimalkan pembelajaran Al-Qur’an melalui integrasi teknologi digital dan pertemuan tatap muka. Aplikasi ini menyediakan layanan pencarian guru profesional untuk tahsin dan tahfidz dengan jadwal fleksibel, sistem pembayaran e-Wallet, serta biaya terjangkau sesuai program yang dipilih. Penelitian ini bersifat kualitatif berbasis Library Research dengan metode deskriptif-analisis melalui sumber jurnal, artikel, dan website. Hasil penelitian berupa prototipe Q-Maps yang menawarkan fitur kemudahan belajar Al-Qur’an sekaligus meningkatkan pemanfaatan teknologi secara positif. Inovasi ini diharapkan dapat menjadi solusi efektif dalam meningkatkan akses dan kualitas pembelajaran Al-Qur’an di Indonesia.